1998
DOI: 10.1093/emboj/17.17.5048
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine string protein (CSP) is an insulin secretory granule-associated protein regulating beta -cell exocytosis

Abstract: 5048

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
87
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 52 publications
7
87
1
Order By: Relevance
“…Instead, in the absence of CSP␣, the calyx synapse developed an age-dependent functional impairment, consistent with a role for CSP␣ as part of a molecular chaperone that makes it possible for synapses to keep running for extended time periods (2). Although this hypothesis was in agreement with previous observations in CSP-deficient flies (4), alternative hypotheses about the function of CSP were proposed based on the phenotype of CSP-deficient flies and on biochemical studies of protein-protein interactions mediated by CSP (7)(8)(9)(10)(11)(12)(13)(14).…”
supporting
confidence: 77%
“…Instead, in the absence of CSP␣, the calyx synapse developed an age-dependent functional impairment, consistent with a role for CSP␣ as part of a molecular chaperone that makes it possible for synapses to keep running for extended time periods (2). Although this hypothesis was in agreement with previous observations in CSP-deficient flies (4), alternative hypotheses about the function of CSP were proposed based on the phenotype of CSP-deficient flies and on biochemical studies of protein-protein interactions mediated by CSP (7)(8)(9)(10)(11)(12)(13)(14).…”
supporting
confidence: 77%
“…These findings demonstrate a crucial role for Csp in neurosecretion (22). In neurons, Csp is associated predominantly with synaptic vesicles (19), and in secretory cells it is found in large dense core or secretory granules (23,24). Studies of membrane dye labeling (25) and neurotransmitter release (26,27) indicated that Csp knockouts exhibit defective neurotransmitter exocytosis; presynaptic endocytosis and vesicle recycling appear to be intact.…”
mentioning
confidence: 89%
“…In fact, although it is clear that CSP plays a significant component in neurotransmission (10,13), its precise role is not yet established. Current reports support a role for CSP in (i) the regulation of exocytosis (41)(42)(43)(44)(45), (ii) the regulation of Ca 2ϩ transmembrane fluxes (46 -51), and (iii) the regulation of folding/refolding of synaptic proteins (13,14). Given that the contributions of vesicular and plasma membrane G␣ s in the various experimental models utilized are not known, it is possible that differences in G␣ s signaling cascades underlie some of the differences observed among these reports.…”
Section: Csp Stimulates Steady-state Hydrolysis Of Gtp By G␣ S -Tomentioning
confidence: 99%